Detection of Mycobacterium tuberculosis in extrapulmonary biopsy samples using PCR targeting IS6110, rpoB, and nested-rpoB PCR Cloning - Meghdadi, Hossein; Khosravi, Azar D.; Ghadiri, Ata A.; Sina, Amir H.; Alami, Ameneh (Frontiers in Microbiology, 2015)
Present study was aimed to examine the diagnostic utility of PCR and nested PCR techniques for the detection of Mycobacterium tuberculosis (MTB) DNA in samples from patients with extra pulmonary tuberculosis (EPTB). In total 80 formalin-fixed, paraffin-embedded (FFPE) samples comprising 70 samples with definite diagnosis of EPTB and 10 samples from known non- EPTB on the basis of histopathology examination, were included in the study. PCR amplification targeting IS6110, rpoB gene and nested PCR targeting the rpoB gene were performed on the extracted DNAs from 80 FFPE samples. The strong positive samples were directly sequenced. For negative samples and those with weak band in nested-rpoB PCR, TA cloning was performed by cloning the products into the plasmid vector with subsequent sequencing. The 95% confidence intervals for the estimates of sensitivity and specificity were calculated for each method. Fourteen (20%), 34 (48.6%) and 60 (85.7%) of the 70 positive samples confirmed by histopathology, were positive by rpoB-PCR, IS6110- PCR and nested-rpoB PCR, respectively. By performing TA cloning on samples that yielded weak (no.=8) or negative results (no.=10) in the PCR methods, we were able to improve their quality for later sequencing. All samples with weak band and 7 out of 10 negative samples, showed strong positive results after cloning. So nested-rpoB PCR cloning revealed positivity in 67 out of 70 confirmed samples (95.7%). The sensitivity of these combination methods was calculated as 95.7% in comparison with histopathology examination. The confidence intervals for sensitivity of the PCR methods were calculated as 11.39-31.27% for rpoB-PCR, 36.44-60.83% for IS6110- PCR, 75.29-92.93% for nested-rpoB PCR and 87.98-99.11% for nested-rpoB PCR cloning. The 10 true EPTB negative samples by histopathology, were negative by all tested methods including cloning and were used to calculate the specificity of the applied methods. The confidence intervals for 100% specifi